2017
DOI: 10.15171/jnp.2018.01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium hydrogen sulfide (a H2S donor) on acute kidney injury

Abstract: Implication for health policy/practice/research/medical education:Hypertension and hyperuricemia are common problems in elderly patients. These problems could be accelerated decrease in glomerular filtration rate (GFR) with aging. It is suggested that lowering uric acid with allopurinol could be beneficial to prevent chronic insufficiency in the elderly patients with hypertension. Please cite this paper as: Mottaghi P. Renoprotective impact of allopurinol in elderly patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The findings have revealed that H2S affected renal function and ameliorated multiple kidney disorders including nephrotoxicity, renal ischemia/reperfusion injury, and obstructive nephropathy (7). In addition, prescription of H2S alleviates STZ-induced diabetic retinopathy through suppressing inflammation and eliminating oxidative stress (8).…”
Section: Introductionmentioning
confidence: 99%
“…The findings have revealed that H2S affected renal function and ameliorated multiple kidney disorders including nephrotoxicity, renal ischemia/reperfusion injury, and obstructive nephropathy (7). In addition, prescription of H2S alleviates STZ-induced diabetic retinopathy through suppressing inflammation and eliminating oxidative stress (8).…”
Section: Introductionmentioning
confidence: 99%